Life-history calibration of social hierarchies: Childhood adversity predicts leadership preference through relational social investment. (April 2022) - Zhu, Nan; Chen, Bin Bin; Lu, Hui Jing; Chang, Lei
Abstract: One approach to understanding leadership styles in human society is through the lens of followers' preferences. From a life history perspective, followers from different backgrounds may develop different psychological traits and social connections that are compatible with the type of future environments that they expect following childhood experiences. This psychosocial life-history profile of the follower, representing different domains of fitness investment, predisposes them to preferences for dominance-style or prestige-style leadership. We tested multiple aspects of followers' life-history profiles as potential mediators between childhood adversity and leadership preferences in hypothetical scenarios in two studies using multisite samples in Mainland China. Study 1 ( N  = 898) focused on childhood economic conditions, and Study 2 ( N  = 1233) examined childhood resource insecurity and negative life events as independent indicators of childhood adversity. The results indicated an association between childhood adversity and a preference for dominant (rather than prestigious) leaders that was mediated by indicators of relational social investment but not by indicators of intellectual, long-term reproduction, or generalized social investment. This finding represents a new direction for research into leadership preferences as well as the application of life-history theory to social psychology. Highlights: People with more adverse childhoods are more likely to endorse dominant leaders. Relational social investment is a key mediator of this relationship. Early adversity does not necessarily undermine intellectual development investment. Not all future-oriented investment predicts a preference for prestigious leaders.